Methods of using interactive methods in the formation of computational skills in elementary school students - Usmanova Zulfiya Ilkhomovna (Zien Journals, 2022)
The article describes the methods and importance of using interactive educational methods in the formation of calculation skills of elementary school students in mathematics classes.
Keywords: Mathematics; interactive method; calculation skills; activation